2010
DOI: 10.3109/09553000903564067
|View full text |Cite
|
Sign up to set email alerts
|

Histamine protects bone marrow against cellular damage induced by ionising radiation

Abstract: Histamine reduces ionising radiation toxicity on bone marrow cells being a suitable candidate for use as radioprotector, especially for patients undergoing radiotherapy who are at the risk of bone marrow or small intestine damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…Rats were maintained in our animal healthcare facility at 22-248C and 50-60% humidity on a 12 h light/dark cycle with food and water available ad libitum. To determine the potential radioprotective effect of histamine on SMG, the same experimental procedures that we previously described in detail to evaluate the radioprotective effect on small intestine and bone marrow were used (Medina et al 2007(Medina et al , 2010.…”
Section: Treatment and Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were maintained in our animal healthcare facility at 22-248C and 50-60% humidity on a 12 h light/dark cycle with food and water available ad libitum. To determine the potential radioprotective effect of histamine on SMG, the same experimental procedures that we previously described in detail to evaluate the radioprotective effect on small intestine and bone marrow were used (Medina et al 2007(Medina et al , 2010.…”
Section: Treatment and Irradiationmentioning
confidence: 99%
“…Histamine prevents radiation-induced toxicity in the small intestine by increasing proliferation of damaged intestinal mucosa and also by suppressing apoptosis (Medina et al 2007(Medina et al , 2010. In addition, histamine has the ability to enhance the radiosensitivity of malignant breast cells (Medina et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In this regard, it was reported that histamine significantly protects small intestine and bone marrow, from high doses of ionizing radiation, in 2 models of rodents. [5][6][7] In addition, histamine has the ability to prevent ionizing radiation-induced functional and histological alterations of salivary glands. 8 These features make histamine a suitable candidate as a radioprotector for patients undergoing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have established a radioprotective role of histamine on bone marrow against cellular damage induced by ionizing radiation (Medina et al, 2010). We have also proved that histamine prevents radiation-induced toxicity on small intestine by modulating the antioxidant enzymes expression and by suppressing apoptosis and increasing proliferation of damaged intestinal mucosa (Medina et al, 2007).…”
Section: Ionizing Radiation Enhances the Activity Of Mmps And Cell MImentioning
confidence: 92%